Editor’s Note - Devi, S. Susela; Quah, Chee Heong (Asian Journal of Business and Accounting, 2013)
It is our pleasure to present to you the second issue of Volume 6 of the Asian Journal of Business and Accounting (AJBA). The journal made its debut in 2008 and has continued to publish research work from scholars within Asia and elsewhere relating to issues in the Asian region. We are encouraged by submissions from scholars from many parts of the world and the growing interest in business and accounting research in this region. We are particularly pleased to receive papers from Asia, especially, the emerging economies. In this issue we have included papers from authors from Fiji, Indonesia, Malaysia, Taiwan and Yemen. AJBA is already indexed in SCOPUS, ERA 2012, and MyCite (25/112) 5 year impact factor of 0.063. We are hopeful given the rigour and quality of papers that have been published and also currently under review, that AJBA will soon succeed in its endeavour to be indexed in the Thomson Reuters Web of Science. In this issue five articles are presented. The first paper by Kung et al. (2013) assesses the extent of the allocation of purchase price toward identifiable intangible assets and thus away from purchased goodwill, during the lifetime of approved accounting standard AASB1013: Accounting for Goodwill in Australia (1988-2004). The findings are significant for Asian scholars in the context of IFRS convergence which may make it more acceptable to combine firms across multiple countries into a single sample. The next two papers examine the Islamic institutional setting. Norazlina Abd. Wahab and Abdul Rahim Abdul Rahman (2013) examine the efficiency of zakat institutions in Malaysia. Azhar Abdul Rahman and Abdullah Awadh Bukair (2013) examine the influence of the Shariah supervisory board on the level of corporate social responsibility (CSR) disclosure in a sample of 53 Islamic banks operating in Gulf Co-operation Council countries for the year 2008 based on a disclosure index from the Islamic perspective. The next paper, Tih and Lee (2013) examines consumers’ perceptions of retail store brands and identifies the predictors of purchase intentions for the store brands. The authors highlight the theoretical and managerial implications for academics and marketers respectively. The last paper, Rokhim and Susanto (2013) investigates the impact of increasing foreign ownership on performance, competition and Asian Journal of Business and Accounting 6(2), 2013 vii short-term insolvency risk in the Indonesian banking industry. They conclude that foreign ownership appears to impact the Indonesian banking industry favourably, although caution is advised in respect of increasing insolvency risk. We would like to welcome Dr Chan Wai Meng as the new deputy chief editor who assumed duties in July 2013. Our sincere appreciation is extended to all our area editors, members of the editorial board and advisory board and reviewers for their continued support and encouragement. We hope this issue brings AJBA closer to achieving its mission to incrementally provide a voice for scholars embarking on Asia-focused research.